Aspek Pasar dan Pemasaran dalam Rangka Pembangunan Pabrik Pakan Ternak di Sulawesi Tenggara - Aku, Achmad Selamet; Pagala, Muhammad Amrullah (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2011)
A descriptive marketed study was undertaken that aimed to examine the established of Feed Mill in Southeast Sulawesi Province based on the potential marketed and effectively demand condition. The research conducted at Kendari City, Buton, Konawe and Konawe Selatan District from April until September 2010. Research method consisted of preparation, pre-survey, survey, effectively demand analysis and competitively product analysis. The result of this research showed that established of feed mill on Southeast Sulawesi was a suitable location. There were support factors as effectively demand was an increase (33.800.350), and big potential marketed because the commercial feed was supplied from outside on Southeast Sulawesi (South Sulawesi and East Java)